A New Method in Certification of Buildings: BCA Method and a Case Study - Ekinci, Cevdet Emin; Elyigit, Belkis (Mdpi, 2025)
This study investigates the engineering characteristics of a newly commissioned higher education building through the Bioharmological Conformity Assessment (BCA) method, specifically using the 2020vEB version. The BCA is a novel evaluation approach that assesses whether a building aligns with the identity of its users and its intended function. The engineering attributes of the structure were assessed across 12 core criteria, encompassing a total of 600 individual parameters. Findings from the BCA inspection indicate that the newly completed building falls into the category of Near-Standard Building/Minor Modifications Required. The BCA score was calculated as 398.73, corresponding to a deficiency rate of 25.50%. Notably, significant shortcomings were observed in categories such as user identity and intended use, Physical Characteristics of the Space, and Ecological and Seismological Suitability. Consequently, targeted improvements are necessary to align the building with bioharmological principles, requiring only minor adjustments to rectify the identified deficiencies.
Keywords: Bioharmological Conformity Assessment (BCA); bioharmology; bioharmological buildings; higher education architecture; engineering assessment of buildings